Fertility Control in a Risk Society : Analysing Contraception Choice of Urban Elites in India - Husain, Zakir; Dutta, Mousumi (SpringerBriefs in Population Studies,, 2017)
This book analyses the reasons for relying on behavioural contraception methods among urban 'elites' in India and examines their efficacy in controlling fertility. It also traces variations in contraception choice over the reproductive cycle of women. Although researchers and policy makers generally equate reliance on behavioural contraceptive methods with low levels of education and awareness and lack of desire to control fertility, this perception has been questioned in recent years. The authors' analysis of the first three rounds of the National Family Health Survey (NFHS) data in India reveals that behavioural contraceptive methods are popular in eastern India. Moreover, it is urban educated women who rely on behavioural methods, and are apparently able to regulate fertility quite effectively with such methods. NFHS data, however, has some limitations and this motivates the authors to explore birth control methods through primary surveys of currently married graduate women in Kolkata. The use of behavioural contraception methods is a little researched area globally and this is the first book focusing on the topic in India.